Rethinking distance learning activities: a comparison of transactional distance theory and activity theory - Kang, Haijun; Gyorke, Allan S. (My University, 2011)
Despite its invaluable guidance to distance education development, transactional distance (TD) theory is not seamlessly synchronised with current field practice and lacks a social component. After it has provided over 30 years of guidance, there is now a need to re-appraise TD’s propositions about distance learning activities. The social–cultural aspects of the distance learner need to be highlighted because social learning is prominent in today’s practice. To address this concern, we compared TD with a social science theory – cultural–historical activity theory. This cultural–historical activity theory provides a different lens for us to explore distance learning activities – a social lens. We compare the major concepts of the two theories and illustrate some areas of compatibility. We explore the contradictions that arise from the collision of these two theories and recommend future directions for research.
Keywords: Transactional distance; Interaction; Activity theory; Mediation; Artefact activity